A SUDENE de Celso Furtado na reforma do Estado (1959-1964) - Pio Júnior, Edson Santos. (2018)
The Brazilian public administration was marked by three major reforms: patrimonialist, bureaucratic and managerial. Reforms happen for a variety of purposes, leaving institutions with their own brands, whether for improving their strategic, structural or operational capabilities across the nation. Sometimes large projects of national prominence are possible, as was Sudene by Celso Monteiro Furtado. During the government of Juscelino Kubitschek (1956 - 1961), Furtado idealized and projected the Sudene, organ in which would put in practice his theories. It was up to him to elaborate the agency's strategy of action, which was defined entirely from the report presented in his 1959 Northeast operation. Many scholars refer to Furtado's Sudene (1959-1964) as a point the renewal nature of which stands out in the public administration and for this reason must be carefully studied. For Furtado, Sudene represented more than one organ, or according to his words: "the project aimed at building a decent country" (FURTADO, 2011, 69). Due to the vastness of the documents and the wide work left by Furtado on the subject, this study aims to discuss and investigate the role of Sudene in the State Reform from the perspective of Celso Furtado, in order to clarify the following question: What represents the Sudene by Celso Furtado for the State Reform? To this end, we divide our data analysis into four main subsections and four other sub-sections derived, aiming to perform the analysis, consolidate explanations, promote the discussion, and ultimately understand. With these bases in place, we will begin our discussion of historical research on the Sudene of Celso Furtado in the reform of the State (1959-1964).